Neuropsychological Features of Children and Adolescents With Mitochondrial Disorders: A Descriptive Case Series - Riquin, Elise; Barth, Magalie; Le Nerzé, Thomas; Pasquini, Natwin; Prouteau, Clement; Colin, Estelle; Amati Bonneau, Patrizia; Procaccio, Vincent; Van Bogaert, Patrick; Duverger, Philippe; Bonneau, Dominique; Roy, Arnaud (Frontiers in Psychiatry, 2022)
Background Mitochondrial disorders (MD) are metabolic diseases related to genetic mutations in mitochondrial DNA and nuclear DNA that cause dysfunction of the mitochondrial respiratory chain. Cognitive impairment and psychiatric symptoms are frequently associated with MD in the adult population. The aim of this study is to describe the neuropsychological profile in children and adolescents with MD. Methods We prospectively recruited a sample of 12 children and adolescents between February 2019 and February 2020 in the Reference Center for Mitochondrial Disorders of Angers (France). Participants and their parents completed an anamnestic form describing socio-demographic data and completed the WISC-V (Wechsler Intelligence Scale for Children, 5th edition) and the Parent and Teacher forms of the BRIEF (Behavior Rating Inventory of Executive Function). Results In our sample, the mean IQ (Intellectual Quotient) score was 87.3 ± 25.3. The score ranged from 52 to 120. Concerning executive functions, a significant global clinical complaint was found for parents (six times more than normal) and to a lesser extent, for teachers (among 3 to 4 times more). Levels of intelligence and executive functioning were globally linked in our cohort but dissociation remains a possibility. Conclusion The results of this study show that MD can be associated to neuropsychological disorders in children and adolescents, especially regarding the intelligence quotient and the executive function. Our study also highlights the need for regular neuropsychological assessments in individuals with MD and developing brains, such as children and adolescents.